Effect of laser radiation on catalase, plasma coagulant, hemolysin, biofilm and Staphylococcus aureus resistance to antibiotics isolated from suppurative keratitis (Journal of the College of Basic Education, 2022)
This study aimed to investigate some virulence factors (hemolesin enzyme, biofilm, catalase enzyme and plasma coagulant enzyme), as well as the sensitivity to antibiotics of S. aureus bacteria isolated from Keratitis infections before and after exposure to the effect of nemodium laser radiation. Also study its plasmid content.One hundred and twelve samples were collected from patients suffering from purulent keratitis, from educational laboratories at Ibn Al-Haytham Eye Hospital in Baghdad for the period from October 2012 to February 2013, where 21 (18.75%) isolates of S. aureus were obtained from the total isolates. bacteria that were isolated.